Sex-dependent differences in type I IFN-induced natural killer cell activation - Pujantell, Maria; Skenteris, Nikolaos-Taxiarchis; Claussen, Janna Marieke; Grünhagel, Benjamin; Thiele, Rebecca-Jo; Altfeld, Marcus (Frontiers in Immunology, 2023)
Natural killer (NK) cells are important antiviral effector cells and also involved in tumor clearance. NK cells express IFNAR, rendering them responsive to Type I IFNs. To evaluate Type I IFN-mediated modulation of NK cell functions, individual Type I IFNs subtypes were assessed for their ability to activate NK cells. Different Type I IFN subtypes displayed a broad range in the capacity to induce and modulate NK cell activation and degranulation, measured by CD69 and CD107a expression in response to leukemia cell line K562. When including biological sex as a variable in the analysis, transwell co-cultures of NK cells with either male- or female-derived PBMCs or pDCs stimulated with the TLR7/8 agonist CL097 showed that NK cells were more activated by CL097-stimulated cells derived from females. These sex-specific differences were linked to higher CL097-induced IFNα production by pDCs derived from females, indicating an extrinsic sex-specific effect of Type I IFNs on NK cell function. Interestingly, in addition to the extrinsic effect, we also observed NK cell-intrinsic sex differences, as female NK cells displayed higher activation levels after IFNα-stimulation and after co-culture with CL097-stimulated pDCs, suggesting higher activation of IFNα-signaling transduction in female NK cells. Taken together, the results from these studies identify both extrinsic and intrinsic sex-specific differences in Type I IFN-dependent NK cell functions, contributing to a better understanding of sex-specific differences in innate immunity.